2014
DOI: 10.1016/j.phytochem.2013.12.010
|View full text |Cite
|
Sign up to set email alerts
|

Metabolomics in melon: A new opportunity for aroma analysis

Abstract: Graphical abstractMelon fruit value is highly influenced by aroma. A simple and robust method of trapping volatile organic compounds combined with detection via thermal desorption (TD)-GC–MS has been developed. Principal component analysis of aroma profiles permitted the characterisation of distinct and closely related melon cultivars according to aromatic quality and shelf life.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
54
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 74 publications
(58 citation statements)
references
References 43 publications
(88 reference statements)
3
54
0
Order By: Relevance
“…1 and Table S1 mouth when eating tomato. Similarly low temperatures have also been used in headspace analysis of volatiles in other fruit species (Allwood et al 2014). The temperatures of 50 and 80°C have been widely used in the literature for volatile analysis of tomato (Maul et al 2000;Tandon et al 2003;Tikunov et al 2005;Baldwin et al 2008;Zanor et al 2009).…”
Section: Effect Of the Temperaturementioning
confidence: 99%
“…1 and Table S1 mouth when eating tomato. Similarly low temperatures have also been used in headspace analysis of volatiles in other fruit species (Allwood et al 2014). The temperatures of 50 and 80°C have been widely used in the literature for volatile analysis of tomato (Maul et al 2000;Tandon et al 2003;Tikunov et al 2005;Baldwin et al 2008;Zanor et al 2009).…”
Section: Effect Of the Temperaturementioning
confidence: 99%
“…Therefore, the performance of this sampling methodology is expected to be representative of Twister ™ sampling. The PDMS sorbent by itself, not coated on SBSE, was used for a number of applications as well [41, 42]. …”
Section: Resultsmentioning
confidence: 99%
“…Volatile analysis indicated that the melon aroma resulted from acetones, non-acetone esters, sulfur-containing compounds, alcohols, and aldehydes [24]. Important chemicals known to cause a melon aroma are cis-3-hexen-1-ol, cis-6-nonenal, 3,6-nonadien-1-ol, and trans,cis-2,6-nonadienal [24,25]. GC analysis suggested that strains MS1 and MS2 produce these four major melon-aroma chemicals.…”
Section: Discussionmentioning
confidence: 99%